Theory and practice of natural computing : 7th International Conference, TPNC 2018, Dublin, Ireland, December 12-14, 2018, Proceedings /: 7th International Conference, TPNC 2018, Dublin, Ireland, December 12-14, 2018, Proceedings. (2018) - Unknown
No abstract available